INTERACTION BETWEEN THE PARAMETERS OF HYDROSTATIC PRESSURE AND TEMPERATURE ON ASPARTASE OF ESCHERICHIA COLI - Haight, Roger D. (1962)
Haight, Roger D. (University of Nebraska, Lincoln) and Richard Y. Morita. Interaction between the parameters of hydrostatic pressure and temperature on aspartase of Escherichia coli. J. Bacteriol. 83:112–120. 1962.—The data obtained from studies of an aspartase preparation and aspartase in cells of Escherichia coli indicate that there is an interaction between the parameters of hydrostatic pressure and temperature. Pressure was found to decrease aspartase activity at 45 C and lower in vitro and below 53 C in vivo, thereby indicating that when the enzyme-substrate complex is formed there is an increase in molecular volume which is counteracted by pressure. Above 53 C in vivo and above 45 C in vitro, temperature probably starts the unfolding process of the enzyme to expose more reactive sites, while pressure then pushes the enzyme and substrate into closer proximity with each other. Thus, pressure stimulated activity and also prevents further unfolding of the enzyme. Since the enzyme preparation retains about the same level of activity after being subjected first to 1000 atm at 56 C, the aspartase probably refolds into its original configuration or one similar to it, when subjected to 1 atm at 37 C. In all cases, the presence of the substrate was found necessary to protect aspartase from thermal inactivation or denaturation.